cDNA isolation and characterization of two vitellogenin genes in the Chagas' disease vector Triatoma infestans (Hemiptera, Reduviidae) - Blariza, María José (2014)
Two vitellogenin genes (Vg1 and Vg2) were identified in the Chagas' disease vector Triatoma infestans. The putative coding sequence corresponding to Vg2 was found to be 5553 bp long, encoding 1851 amino acids in a single open reading frame. The comparative analysis of the deduced amino acid sequences from Vg1 and Vg2 cDNA fragments of T. infestans revealed 58.94% of identity with 76.43% of homology. The phylogenetic tree based on the complete Vg amino acid sequences of hemimetabolous insects unambiguously supported two clusters, one consisting of Vg sequences from dictyopteran and the other containing Vg sequences of hemipteran. The Vg1 and Vg2 mRNAs were detected in fat bodies and ovaries of adult females with the highest levels of both Vg transcripts in the first tissue. Quantitative PCR showed low expression of Vg2 in head and muscle of adult females, while the Vg1 transcript was not present in these organs. Neither Vg1 nor Vg2 was expressed in fifth instar nymph fat bodies or in adult male fat bodies, heads, and muscles.